STUDI FENOMENOLOGI KEJADIAN PREEKLAMPSIA DI RSUD CILACAP TAHUN 2015-2017 - ., Johariyah (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2018)
The World Health Organization (WHO) estimates that 16% of maternal deaths are due to hypertensive disorders in pregnancy, where eclampsia is the most common cause. Every six minutes a mother dies from preeclampsia in the world. The cause of maternal death in Cilacap District from 36 cases were bleeding (28%), preeclampsia-eclampsia (24%), and infection (11%). The prevalence of preeclampsory occurrence is about 8.4% in Ethiopia, lower than that of Birmingham, which is 11.9%, Nigeria 16% and Finland at 13.9%, the prevalence of preeclampsia in Indonesia is 12.7%. This research is done by using descriptive method with cross sectional approach, that is data taking done in one stage. The analysis in this study was conducted by looking at frequency distribution of preeclampsia occurrence based on predisposing factor of preeclampsia consisting of age, parity, body mass index (IMT), pregnancy interval, gemelli, history of hypertension and previous preeclampsia history. The results showed that there was an increase of preeclampsia incidence in RSUD Cilacap from 2015 until 2017 with an increase of 2.1% and 20.2%. By age, in 2015 it was found that the average preeclampsia occurred at the age of 30.25 years, the year 2016 the average age of the mother of preeclampsia was 32.15 years and in the year 2017 the average age of 32.23 years. Based on IMT it is found that from 2015 to 2017 preeclampsia occurs in women with an average BMI of 27.2; 26.1 and 29.4. The incidence of preeclampsia in primigravida from 2015 to 2017 was 35.6%, 37% and 40.7%. The 10-year pregnancy interval in women with preeclampsia in Cilacap Hospital 2015 to 2017 was 12.4%; 8.6% and 12.1%. The incidence of preeclampsia in mothers with Gemelli pregnancy from 2015 to 2017 is 8%; 5.4% and 9.3%. While the incidence of preeclampsia in women with preeclampsia history in previous pregnancy was 8.1%; 6% and 13.7%. Keywords: preeclampsy, events, factors